Action of Salicylic Acid on Plant Growth - Li, Aixia; Sun, Xue; Liu, Lijing (Frontiers in Plant Science, 2022)
The phytohormone salicylic acid (SA) not only is a well-known signal molecule mediating plant immunity, but also is involved in plant growth regulation. However, while its role in plant immunity has been well elucidated, its action on plant growth has not been clearly described to date. Recently, the increasing evidence indicated that SA plays crucial roles in regulating cell division and cell expansion, the key processes that determines the final stature of plant. This review summarizes the current knowledge on the action and molecular mechanisms through which SA regulates plant growth via multiple pathways. It is here highlighted that SA mediates growth regulation by affecting cell division and expansion. In addition, the interactions of SA with other hormones and their role in plant growth determination were also discussed. Further understanding of the mechanism underlying SA-mediated growth will be instrumental for future crop improvement.